2021
DOI: 10.3390/educsci11100615
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Gifted Education Pedagogy to Develop Talents, Gifts, and Creative Productivity

Abstract: Providing challenging and engaging learning opportunities is one way to motivate students to learn. In this article, we discuss the contributions of the gifted education field to the development of enrichment pedagogy and identify several different types of these engaging instructional strategies, including interest-based learning pedagogy, differentiation and curriculum compacting, project-based learning, open-ended choice, and the application of creative productivity to students learning. We identify this sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…The analysis indicated that participants thought the applications in the technology-based program offered many benefits such as preparing for the lesson, supporting the class, differentiating instruction, increasing motivation, enriching the lesson, evaluating, and communicating. These outcomes are similar to many studies in the literature (Guilbault & McCormick, 2021;Kontostavlou & Drigas, 2019;Reis et al, 2021;Sayı & Soysal, 2022). Moreover, they detailed information about the use of the applications in the project-based learning process and explained the benefits of the tools provided in specific for each separately.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis indicated that participants thought the applications in the technology-based program offered many benefits such as preparing for the lesson, supporting the class, differentiating instruction, increasing motivation, enriching the lesson, evaluating, and communicating. These outcomes are similar to many studies in the literature (Guilbault & McCormick, 2021;Kontostavlou & Drigas, 2019;Reis et al, 2021;Sayı & Soysal, 2022). Moreover, they detailed information about the use of the applications in the project-based learning process and explained the benefits of the tools provided in specific for each separately.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the similarity between the main objectives of the gifted education program and the student outcomes expected to be gained in the project production and management process, it can be said that the students who find the gifted program to be effective and of good quality can achieve the specified program objectives more than the students who do not find it to be of good quality, and that consequently, they are more effective and competent in project production and management. It has been determined that students who deal with independent and small group projects, which are at the center of the gifted education program, perceive their projects as interesting and useful and believe that they contribute to their continuing interests and perceptions of pleasure in the future (Reis et al, 2021 ). In addition, students are the most basic products of the program they evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…Other curriculum developers and researchers have identified models to formulate decisions to differentiate a curriculum. Renzulli presents the Triad Model to differentiate a curriculum, which emphasizes the presentation of general exploratory enrichment activities (Type 1), the development of cognitive skills such as critical thinking and research skills (Type 11), and individualized or group investigations (Type 111) [7]. Carol Tomlinson and her colleagues describe a Parallel Curriculum model that defines four pathways to differentiation: Core Curriculum; Curriculum of Connections, or identifying how skills and concepts from curricular subjects or disciplines can be integrated; Curriculum of Practice, which emphasizes learning centered on a discipline; and Curriculum of Identify, which enables the development of personal interests and abilities [8].…”
Section: Conflicts Of Interestsmentioning
confidence: 99%